Coir, wood shavings and peat as growth substrates for arctic bramble - Tero Tommila; Antti Kämäräinen; Harri Kokko; Pauliina Palonen (Mires and Peat, 2022)
Methods for protected container cultivation of arctic bramble (Rubus arcticus L.) are currently under development. The aim of this study was to evaluate coir and wood shavings as alternatives to peat-based growth substrate (growing medium) in the intensive greenhouse cultivation of arctic bramble. The substrates used were a commercial coir mix (Coir), wood shavings from sodium silicate impregnated wood (Wood), a mixture of 95 % horticultural peat and 5 % perlite (HPP), and a mixture of 80 % peat and 20 % wood shavings (HPWood). Growth and fruit yield were highest in HPP, followed by Coir and HPWood, and were most severely reduced in Wood. Shoot nutrient analyses and soil drainage water observations suggested that the poor performance of Wood was mainly caused by release of sodium silicate into the rooting zone due to unsuccessful substrate processing. A higher proportion of the pore space in Wood was air-filled compared to other substrates, possibly limiting water availability. Overall, the suitability of both coir and wood shavings as growth substrates for arctic bramble was relatively low. However, it is likely that the poor performance of wood shavings was caused largely by inappropriate preparation. For wood waste to be useful as a growth substrate, the wood material should be specially processed for that purpose.